Ženský leadership v rodinném podnikání: poznatky z kvalitativního výzkumu v České republice - Kolouchová Daniela; Machek Ondřej (Trendy v podnikání, 2016)
Family business belongs to the emerging areas of research in the Czech Republic and the role of female managers in Czech family firms has never been investigated. At the same time, women and their role in family firms appears to be an underresearched area in most countries around the world. The goal of this article is to examine the main motivations of family entrepreneurship, to explore managerial competences of female managers and differences between male and female leadership style, and to get to know how the work-family conflicts are solved. Using semi-structured in-depth interviews with ten female CEOs of Czech family firms, the authors found that the basic prerequisites of family firms’ success are a clear division of roles, a continuous preparation of children for future succession, and spousal support. The integrative role of female CEOs can mitigate conflicts and improve family firms’ productivity. Female managers also seem to be more risk-averse and long-term oriented. Women in managerial position are very realistic in financial decisions. They are clearly more prudent, carefully evaluating all possible alternatives and risks. The important managerial ability of female family firm owners and directors is an effort to carry out an honest business with no unfair motives, despite the fact the respondents noticed such behavior in the case of men. If women really contribute to the productivity and continuity of Czech family firms, the results provide some justification for supporting career promotion of women and supporting family entrepreurship in general.